Evaluation of the Brief Alcohol Withdrawal Scale Protocol at an Academic Medical Center. Issue 5 (September 2019) - Lindner, Brian K.; Gilmore, Vi T.; Kruer, Rachel M.; Alvanzo, Anika AH.; Chen, Edward S.; Murray, Paula; Niessen, Timothy; Perrin, Keisha; Rastegar, Darius A.; Young, Samantha; Jarrell, Andrew S.
Abstract : Objectives: The standard of care for treatment of alcohol withdrawal is symptom-triggered dosing of benzodiazepines using a withdrawal scale. Abbreviated scales are desired for clinician efficiency. The objective of this study was to evaluate the use of the 5-item Brief Alcohol Withdrawal Scale (BAWS) protocol. Methods: This single-center, retrospective, observational, cohort study assessed patients ordered the BAWS protocol between August 1, 2016 and July 31, 2017. Data were collected on benzodiazepine exposure, duration of treatment, withdrawal severity, agitation, over-sedation, and delirium while being treated for alcohol withdrawal. Comparisons were made to analyze predetermined patient subgroups. Results: Seven hundred ninety-nine patients were initiated on the BAWS protocol. Patients received a median (IQR) of 0 (0–4) lorazepam equivalents (LEs) and were on the BAWS protocol for a median (IQR) of 44.9 (22.4–77.2) hours. Of the patients that received benzodiazepines while on the BAWS protocol, a median (IQR) of 4 (2–11) LEs were given. Seventeen (2.1%) patients had severe withdrawal. Days of agitation, over-sedation, and delirium were minimal, with the median (IQR) of 0 (0–0). Few patients received adjunctive medications for symptom management. Intensive care unit (ICU) patients had more severe withdrawal than non-ICU patients, but received the same cumulative benzodiazepine dose. Conclusions: Most patients on the BAWS protocol received little-to-no benzodiazepines; severe withdrawal, agitation, delirium, or over-sedation were uncommon. This is the first evaluation of the BAWS protocol on a diverse population of hospitalized patients. Abstract : Supplemental Digital Content is available in the text